SPORT: Does Incidental Durotomy Affect Longterm Outcomes in Cases of Spinal Stenosis?. (March 2015) - Desai, Atman; Ball, Perry A.; Bekelis, Kimon; Lurie, Jon; Mirza, Sohail K.; Tosteson, Tor D.; Weinstein, James N.
Abstract : BACKGROUND: Incidental durotomy is a familiar encounter during surgery for lumbar spinal stenosis. The impact of durotomy on long-term outcomes remains a matter of debate. OBJECTIVE: To determine the impact of durotomy on the long-term outcomes of patients in the Spine Patient Outcomes Research Trial (SPORT). METHODS: The SPORT cohort participants with a confirmed diagnosis of spinal stenosis, without associated spondylolisthesis, undergoing standard, first-time, open decompressive laminectomy, with or without fusion, were followed up from baseline at 6 weeks, and 3, 6, and 12 months and yearly thereafter at 13 spine clinics in 11 US states. Patient data from this prospectively gathered database were reviewed. As of May 2009, the mean follow-up among all analyzed patients was 43.8 months. RESULTS: Four hundred nine patients underwent first-time open laminectomy with or without fusion. Thirty-seven of these patients (9%) had an incidental durotomy. No significant differences were observed with or without durotomy in age; sex; race; body mass index; the prevalence of smoking, diabetes mellitus, and hypertension; decompression level; number of levels decompressed; or whether an additional fusion was performed. The durotomy group had significantly increased operative duration, operative blood loss, and inpatient stay. There were, however, no differences in incidence of nerve root injury, mortality, additional surgeries, or primary outcomes (Short Form-36 Bodily Pain or Physical Function scores or Oswestry Disability Index) at yearly follow-ups to 4 years. CONCLUSIONS: Incidental durotomy during first-time lumbar laminectomy for spinal stenosis did not impact long-term outcomes in affected patients. ABBREVIATIONS: SBI, Stenosis Bothersomeness Index;SF-36, Short Form-36;SPORT, Spine Patient Outcomes Research Trial